Employee Engagement and Digital Leadership with Brand Advocacy Mediation on Marketing Performance - Nurdhania Rahayu Rahayu; Dinda Amalia Amalia (ICON Publisher, 2026)
This study examines the influence of employee engagement and digital leadership on marketing performance, with brand advocacy as a mediating mechanism, in the context of micro, small, and medium-sized enterprises (MSMEs). A quantitative approach using partial least squares structural equation modeling was applied to survey data collected from 230 MSME employees. Measurement model evaluation confirmed adequate reliability and validity before assessing the structural relationships through bootstrapping procedures. The results indicate that employee engagement and digital leadership both have significant positive effects on brand advocacy and marketing performance. Brand advocacy shows a strong direct impact on marketing performance and partially mediates the relationships between employee engagement, digital leadership, and marketing performance. These findings suggest that internal psychological conditions and leadership practices influence market outcomes through employees’ voluntary brand-supportive behavior. The study extends the employee-based brand equity perspective by clarifying the behavioral pathway that links internal organizational factors to external performance. From a managerial standpoint, the results emphasize the importance of fostering employee engagement and digitally oriented leadership to strengthen employees’ role as brand advocates. This research integrates engagement, digital leadership, and brand advocacy within a unified framework to explain marketing performance in MSMEs, offering a human-centered perspective on competitiveness in digitally mediated markets.